A study on the relationship between organizational commitments (OC) towards organizational citizenship behavior (OCB) among employees at MARA Terengganu, Malaysia / Maisarah Ismail - Ismail, Maisarah (2016)
Purpose - The purpose of the study is to measure the relationship between organizational commitment and organizational citizenship behavior and also to identify the level of three-component model (TCM) in organizational commitment with organizational citizenship behavior in MARA Terengganu, Terengganu. Design/Methodology - This study utilized convenience sampling techniques. The data collected by using questionnaires that required respondents to rate the suitable answers. It was measured by using five point Likert scales. The comparison has been used by using means. Based on my findings, the factors in the data was analyzed using SPSS 20.0 and its shows that the Three Component Model of Organizational Commitment which are Affective Commitment, Continuance Commitment and Normative Commitment were analyzed in this study and the result showed that there are relationship between Affective Commitment and Organizational Citizenship Behavior and positive relationship between Normative Commitment with Organizational Citizenship Behavior. Organizational Commitment and Organizational Citizenship Behavior of correlational have resulted in a moderate correlation. Findings - The findings indicated that there is significant relationship between organizational commitment and organizational citizenship behavior among employees at MARA Terengganu. Conclusion - The result indicates that the respondents at MARA Terengganu more prefer normative commitment of three component model (TCM) in order to increase the organizational behavior in the organization. Recommendation - Try to use another sampling technique to make the result more clear and practice to prioritized the work activities at other branches so that the result.